The Effect of partnership collaboration on road safety: a case of the National Transport and Safety Authority and the Kenya Police at the Coastal Region of Kenya - Munyao, Maryanne Nduku (Strathmore University, 2022)
There is overwhelming evidence of increased road mortalities within Kenya which has led to the Kenyan government setting up various agencies to enhance road safety. Despite the various measures adopted by both the NTSA and the Kenya Police, there has been minimal improvement of road safety within the country. This research sought to examine whether collaboration between the NTSA and the Kenya Police influences road safety within the coastal region of Kenya. The study specifically reviewed whether standard interoperation, feedback and distribution of labor has an effect on road safety. The research was grounded on the collaboration theory and the three phased model. The study was anchored on the positivism research paradigm with a quantitative descriptive design being utilized in the research. The target population for the survey was 263 officials drawn from the NTSA and the Kenya Police. The sample size for the survey was 207 participants from both institutions. The research adopted a structured research questionnaire in the data collection process. The collected responses were analyzed in the Statistical Package for Social Sciences (SPSS) using descriptive and inferential techniques. The overall regression results established that a positive change in the road safety within the coastal region of Kenya, was predicted by the level of collaboration between the NTSA and the Kenya Police. The study concluded that standard interoperation and feedback had a significant effect on road safety in the region. However, it was found out that distribution of labor does not significantly predict road safety in the region. The study recommends that the NTSA and the Kenya Police in collaboration with other agencies should strive to modernize with the use of ICT, road safety measures, have a larger work force thus adequate deployment of officers and improve community participation in reporting and identifying road offenders that can enhance road safety. The study was limited to three practices that are anchored on the collaboration theory; standard interoperation, feedback and distribution of labor.
A Thesis submitted in partial fulfillment of the requirements for the award of the Degree of Masters of Business Administration at Strathmore University Business School
Keywords: Collaboration; Feedback; Standard interoperation; Distribution of labor; Road safety